Nematode Management in Potatoes (Irish or White) - Joseph W. Noling (EDIS)
Nematode species and population levels, incidence of soil-borne diseases and insects, soil moisture at field preparation time, and the intended market for the potatoes can all affect the choice of nematode control measures. Growers should use a combination of as many different kinds of control measures as feasible, since none provides perfect protection for the crop. This 7-page fact sheet was written by J.W. Noling and published by the UF Department of Entomology and Nematology, December 2012.